The relevance of the concepts of violence and status to the study of the Selk’nam society of Patagonia, the Land of Fire - de Oliveira, Rodrigo Lima (Seven Editora, 2023)
The analysis of indigenous societies can raise important considerations about Western thought. For this, we seek conceptual equipment that derives from a multidisciplinary basis in the field of humanities that covers areas such as Political Science, Sociology, Anthropology, History, and Philosophy. Thus, the Selk’nam were observed through ethnographic reports — since they are an extinct society. The objective of this work is the description of indigenous society and the purpose of the research is to advance in political theory, especially in issues related to identity, belonging, and status. Thus, an observation was made through four layers: the described society, the political organization, the belief systems, and the concepts related to status and violence. For this, we used the methodology of the rooted theorization of Anne Laperriére and the phenomenological proposal of Amadeo Giorgi. The theoretical framework for the study of violence included the contributions of Hannah Arendt, Pierre Clastres, and Maria Stela Grossi Porto. In turn, the status structure was analyzed by Marcel Mauss and, predominantly, Max Weber. DOI: https://doi.org/10.56238/devopinterscie-048